Unveiling Students of Midwifery Needs towards HOTS-based English for Specific Purpose Reading Materials - Koller, Muthia Zahranisa; Mirizon, Soni; Eryansyah, Eryansyah (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2024)
Higher-order thinking skills (HOTS) are crucial in today`s fast-paced world of healthcare education. Healthcare professionals frequently encounter complex, unpredictable situations. HOTS enables them to assess patient conditions, make informed decisions, and solve problems effectively. These skills need to be taught to students of healthcare education. One of the ways is through the provision of HOTS-based learning materials in teaching English for specific purposes. The primary goal of this study was to investigate the students` need for English in relation to their future careers as paramedics. This study explores the needs of DIII Midwifery Study Program students at the Health Polytechnic, Ministry of Health in Palembang. Using a mixed-method approach incorporating both quantitative and qualitative, the research data were gathered using surveys for collecting quantitative data and semi-structured interviews for collecting qualitative data. The data was examined utilizing the Target Situation Analysis, Deficiency Analysis, Present Situation Analysis, and Strategy Analysis criteria for requirements analysis put forward by Hutchinson and Waters (1987). The study revealed that students of the Midwifery Program had a high interest in learning English, especially HOTS-based English reading materials. Additionally, the lecturer of English was also in need of a specific source of English material related to midwifery to support students learning English for specific purposes, as such material was not available in her teaching context.